On-court game-based testing in world-class, top-elite, and elite adult female team handball players - Wagner, H.; Fuchs, P.; Michalsik, L. Bojsen (Translational Sports Medicine, 2020)
The on-court physical performance knowledge of adult female world-class players in team handball is lacking, especially when testing specific physical performance on-court under similar conditions as in competition. Consequently, the aims of the study were to analyse team handball oncourt physical performance in elite, top-elite and world-class female team handball players by using team handball specific testing. Ten elite, eleven top-elite and eleven world-class adult female players performed a team handball game-based performance test. We measured, oxygen uptake, heart rate, blood lactate concentration, ball velocity and jump height in the jump shots as well as running time (in offence, defence, fast break and retreat). Significant differences were found in peak oxygen uptake, heart rate, ball velocity, defence, offence and fast break time between world-class, top-elite and elite players. During breaks, between the high-intensity movements in the game-based performance test, a world-class player had greater increase in oxygen uptake compared to an elite player. The results of the present study clearly indicated the importance of specific agility both in offence and defence, in throwing velocity in the jump shot as well as in aerobic performance to become a world-class adult female team handball player.